Determining Association of Myopia and Primary Open Angle Glaucoma - Admani, Mohammad Uzair; Maree, Ghazi Khan; Mirza, Azfar Ahmed; Rajput, Arsalan Ahmed; Mahesar, Mona Liza; Munawar-Ul-Islam, Sanam; Shaikh, Adil Ali; Zeba, Nudrat (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the association between myopia and primary open-angle glaucoma.Study Design: Comparative cross-sectional study.Place and Duration of Study: Department of Ophthalmology, Liaquat University Hospital Jamshoro from Jan to Jun 2015.Methodology: A sample of 170 diagnosed cases of myopia and 170 subjects without myopia were selected. Inclusion criteria were age 35-60 years, both genders, cases with myopia >1.0 D and controls - without myopic error. Visual status was determined by the Huwitz autorefractor (model 8800) machine. Retinoscopy, Goldmann's Applanation tonometry, gonioscopy, vertical cup to disc (VCD) ratio and visual field defects were detected.Results: Age of group – 1 and–2 was 55.7 ± 8.6 and 52.3 ± 7.3 years respectively (p=0.071). VCD ratio in group-1 was 0.6 ± 0.13 compared to 0.5 ± 0.02 in group-2 (p